Nigeria’s Criminal Justice System: Legal Gaps, Human Rights Concerns, and Comparative Lessons for Reform - Chegwe, Emeke Nelson; Esavwede, Philip Jenigho (Christ University Law Journal, 2025)
Nigeria’s criminal justice system lacks adequate mental health provisions, leading to human rights violations and worsening psychiatric conditions among offenders. This study examines Nigeria’s compliance with international standards, particularly the Mandela Rules, using a descriptive research design. Based on the 2018 prison Audit Report, it examines mental health services, jail regulations, and legal protections. Structured oversight with respect to South Africa, the United States, and Canada has been highlighted through a comparative analysis. South Africa guarantees judicial oversight, whereas Canada’s NCRMD structure ensures rehabilitation. States in the US differ in how they balance treatment and incarceration. Nigeria, in contrast to South Africa and Canada, lacks formal evaluations and reintegration programs and instead depends on administrative discretion. This paper argues for a human rights-based strategy, including legislative safeguards, frequent psychiatric examinations, and rehabilitation programs. The protection of mentally ill offenders, public safety, and justice can all be enhanced by putting these ideas into practice. Nigeria’s mental health legislation will advance if it conforms to international best practices.